2011
DOI: 10.1007/s13361-011-0227-4
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Phospholipids in Formalin Fixed Rat Brain Sections by Matrix Assisted Laser Desorption/Ionization Mass Spectrometry

Abstract: Matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) is a valuable tool for the analysis of molecules directly from tissue. Imaging of phospholipids is gaining widespread interest, particularly as these lipids have been implicated in a variety of pathologic processes. Formalin fixation (FF) is the standard protocol used in histology laboratories worldwide to preserve tissue for analysis, in order to aid in the diagnosis and prognosis of diseases. This study assesses MALDI imaging of phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
72
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 76 publications
12
72
0
Order By: Relevance
“…The increase in LPC and decrease in PC in the AD brains detected in our positive ion mode analysis ( Fig. 5 ) directly resulted from the activation of PLA 2 , which is reported to be hyperactivated in various disease conditions, including AD, Parkinson's disease, ischemia, spinal cord trauma, and head injury (34)(35)(36)(37)(38)(39)(40). It was also reported that increased neuronal activity of PLA 2 converts PC to LPC, which stimulates glial cells and subsequently induces neuroinfl ammation ( 34 ).…”
Section: Discussionmentioning
confidence: 76%
“…The increase in LPC and decrease in PC in the AD brains detected in our positive ion mode analysis ( Fig. 5 ) directly resulted from the activation of PLA 2 , which is reported to be hyperactivated in various disease conditions, including AD, Parkinson's disease, ischemia, spinal cord trauma, and head injury (34)(35)(36)(37)(38)(39)(40). It was also reported that increased neuronal activity of PLA 2 converts PC to LPC, which stimulates glial cells and subsequently induces neuroinfl ammation ( 34 ).…”
Section: Discussionmentioning
confidence: 76%
“…Recently reported phospholipidomic MSI has been achieved that showed no signs of delocalization or interference from the formalin in formalin-fixed tissue. However, an increase in sodium adduct ions was reported as a result of the sodium buffers associated with the formalin fixation protocol [56]. MSI has also been used to identify drugs in formalin-fixed tissue samples, for example confirming the identification of microcrystalline material in histopathologic tissue sections [57].…”
Section: Collectionmentioning
confidence: 99%
“…12,13) For the analysis of lipids, some species may be analyzed with no special pre-treatment of the samples. 14) One should remember that heat stabilization, formalin fixation and microwave irradiation permanently protects samples from enzymatic changes, whereas freezing only preserves the sample state until the temperature is risen and enzymatic processes re-occur.…”
Section: Tissue Stabilizationmentioning
confidence: 99%